2021
DOI: 10.1002/jbt.22798
|View full text |Cite
|
Sign up to set email alerts
|

β‐Asarone suppresses TNF‐α expression through DNA methylation and c‐Jun‐mediated transcription modulation in scratch‐injured neuronal cells

Abstract: This study aimed to investigate the role and possible mechanism of β-asarone in regulating neuronal apoptosis and axonal regeneration. A scratch injury was applied to cell cultures of mouse primary cortical neurons to mimic neuronal injury. The neuronal apoptosis was evaluated by terminal deoxynucleotidyl transferase dUTP nick end labeling staining and western blot analysis of apoptosis-related proteins.The axonal regeneration was assessed by immunofluorescent staining of β-tubulin III and western blot analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These results demonstrate that rTNF-α may be a critical regulator of the barrier that prevents cytotoxic molecules from entering the fetal circulation. Accumulating evidence demonstrates that in cancers, TNF-α stimulates c-Jun through the activation of c-Jun N-terminal kinase (JNK), which is a classical signaling pathway tightly associated with inflammation (18). In this study, we analyzed c-Jun mRNA and protein levels in response to rTNF-α treatment and found that rTNF-α induced c-Jun expression and phosphorylation in a doseand time-dependent manner in Bewo cells, consistent with previous reports demonstrating that TNF-α facilitates a variety of pathophysiological activities through transcriptional and posttranscriptional regulation of c-Jun expression (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that rTNF-α may be a critical regulator of the barrier that prevents cytotoxic molecules from entering the fetal circulation. Accumulating evidence demonstrates that in cancers, TNF-α stimulates c-Jun through the activation of c-Jun N-terminal kinase (JNK), which is a classical signaling pathway tightly associated with inflammation (18). In this study, we analyzed c-Jun mRNA and protein levels in response to rTNF-α treatment and found that rTNF-α induced c-Jun expression and phosphorylation in a doseand time-dependent manner in Bewo cells, consistent with previous reports demonstrating that TNF-α facilitates a variety of pathophysiological activities through transcriptional and posttranscriptional regulation of c-Jun expression (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-asarone represents the cis isomer of asarone. Recent findings suggest that this phenylpropanoid can regulate different molecular mechanisms to retrieve axonal regeneration and apoptosis in mouse primary cortical neurons after scratch injury damage [129]. In detail, β-asarone can inhibit JNK-dependent c-jun phosphorylation and activation, which ultimately is unable to interact with the promoter region of the TNF-α gene to stimulate its transcription.…”
Section: Acorus Tatarinowii Eomentioning
confidence: 99%
“…In detail, β-asarone can inhibit JNK-dependent c-jun phosphorylation and activation, which ultimately is unable to interact with the promoter region of the TNF-α gene to stimulate its transcription. Moreover, β-asarone induces the upregulation of UHFR1 protein that, in turn, recruits DNA methyltransferase 1 to induce TNF-α promoter methylation and thus gene expression silencing [129].…”
Section: Acorus Tatarinowii Eomentioning
confidence: 99%
“…Previous studies have shown that β-asarone exhibits good pharmacological effects on the astrocyte-neuronal cell system. Our research team previously found that β-asarone ether exerts a protective effect on PC12 cell injury induced by amyloid β 1-42 (Aβ 1-42 )-activated astrocytes [8], which was con rmed by Zhenwan Li and Yi M [9,10]. However, the mechanism underlying the β-asarone-mediated regulation of astrocyte-neuron system is not clear yet.…”
Section: Introductionmentioning
confidence: 99%